(untitled) (Research, Society and Development, 2023)
Objective: To identify the scientific evidence on the use of medicinal plants by the elderly diabetic and hypertensive people and to describe potential interactions between plants and drugs used. Methods: This is an integrative literature review, whose searches were conducted in the following databases: BDENF, LILACS, MEDLINE. Results: Fourteen articles were included. Analysis was performed using an evaluative matrix that considered the characterization of the study, answers to the research question and level of evidence. After the pre-analysis, material exploration and interpretation two categories were originated, which allowed us to synthesize the findings: Main medicinal plants used by hypertensive and/or diabetic elderly people and Potential plant-drug interactions. Conclusion: The findings of the present study indicate that the main medicinal plants mentioned present greater drug interactions in the daily life of the elderly. Also, for the need of health professionals to be prepared to know how to guide the elderly diabetic and hypertensive population in their consultations.